ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN RIIL MOBIL TOYOTA KIJANG INNOVA DI KOTA SEMARANG - Bagus Ardi Kurniawan; Fitrie Arianti (Universitas Diponegoro, 2013)
The average increase demand of Toyota Kijang Innova in Semarang city from year to year is quite significant. At first, rising demand in Toyota Kijang Innova relatively high are viewed because of the rise in per capita income. but changes in per capita income each year always increase not corresponding to changes of on demand Toyota Kijang Innova, so that suspected there is another factor affecting change demand Toyota Kijang Innova in the Semarang city. This research done with purpose to test factors affecting demand Toyota Kijang Innova, was the Toyota Kijang Innova, income consumers, post traded services and another car prices by using data primary. A method of data acquisition techniques with the method of cluster sampling questionnaires given to consumers of Toyota Kijang Innova at any authorized dealers of Toyota in the city of Semarang. This research was done using OLS estimation method with two variables, using dummy variables. Post traded services, and the price of other cars that had previously been done in the form of a classic assumption test heteroskedastisitas test and test multicoliniearity.The results showed that there is a positive and significant effect between price Toyota Kijang Innova with the request, this influence is elastic. In addition, there is a positive and significant effect between income consumers with Toyota Kijang Innova requests where this influence is also elastic. It can be concluded that Toyota Kijang Innova is a normal goods to consumers Toyota Kijang Innova in the city of Semarang. Meanwhile, post traded services and the price of another car not affect the demand Toyota Kijang Innova.